Selección de estaciones de muestreo para una red de monitoreo de calidad de agua en la hoya de Loja - Arteaga Marín, Juan Gabriel (2014)
Water quality monitoring is one of the basic conditions for water management activities in watersheds. The present study focuses on the selection of sampling stations for a water quality monitoring network for the streams of the hoya of Loja applying GIS tools. Selection of sampling points was performed using multi-criteria analysis (scoring method) from derived spatial information, grouped and represented in five variables: potential nonpoint – source pollution, historical water quality, potential point source pollution, water use and stream order in the drainage network. A total of 194 potential sampling points were obtained and then prioritized according to their monitoring importance score and an accessibility analysis. The 194 points were reduced to 68 critical sampling points and proposed for the design of water quality monitoring network of the hoya of Loja.